The Omnibus Law Concept and Changes in Substantive Provisions in Law Number 17 of 2023 on Health - Syai Saladin Usman; Arrie Budhiartie (JURNAL LEGALITAS, 2026)
The omnibus law concept refers to an approach that consolidates numerous regulations into a single regulatory framework. In 2023, the government applied this concept to Law Number 17 of 2023 on Health, with the objective of reforming health services to improve the health status of the Indonesian population and to address current and future health issues. However, various problems occurred during the drafting process, which affected the substance contained in the Health Law. The purpose of this study is to analyze the omnibus law concept and its influence on the Health Law. The research method employed is normative juridical, using a statutory approach by examining the Health Law and Government Regulation Number 28 of 2024 concerning the implementing regulations of the Health Law, as well as a conceptual approach. The results of this study indicate that the drafting process of the Health Law was conducted within a short period and did not adequately observe the principle of public participation, limiting public access to information regarding the substance of the law. This condition generated polemics within society and influenced substantive changes, including concerns from professional organizations that the Health Law removes their authority to supervise medical and health personnel, the expansion of authority in the supervision of the distribution of drugs and medical devices by BPOM, and the emergence of legal protection for pharmacists not only when performing their duties in pharmacies but also in extraordinary circumstances. The novelty of this research lies not only in examining the legislative process but also in analyzing substantive changes within the Health Law. Accordingly, this study provides a new perspective for future empirical research to examine the implementation of the Health Law.